2018
DOI: 10.1111/dth.12586
|View full text |Cite
|
Sign up to set email alerts
|

Etoposide as a single agent in the treatment of mycosis fungoides: A retrospective analysis

Abstract: Several chemotherapy agents have shown efficacy in the treatment of mycosis fungoides (MF). In the literature, there is limited data on the use of single agent etoposide for MF. We aimed to retrospectively review our experience with single agent etoposide in the treatment of advanced-stage or refractory early-stage MF with focus on analyzing its efficacy and safety. We included 13 MF patients who were treated with single agent etoposide. Patients were identified through the Cutaneous T Cell Lymphoma Database o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
6
2
Order By: Relevance
“…11 Indeed, a previous retrospective study suggested that the efficacy rate of etoposide monotherapy for the treatment of MF was 69% (95% CI: 42.0%-87.6%), and the median duration of response was 43 (5-60) weeks. 12 Interestingly, in the present case series of MF treated with etoposide-based therapy as post mogamulizumab monotherapy, the efficacy rate and median duration of response tended to be better than in a previous report. 12 Not only efficacy, but also safety profiles are important to evaluate the clinical use of mogamulizumab monotherapy.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…11 Indeed, a previous retrospective study suggested that the efficacy rate of etoposide monotherapy for the treatment of MF was 69% (95% CI: 42.0%-87.6%), and the median duration of response was 43 (5-60) weeks. 12 Interestingly, in the present case series of MF treated with etoposide-based therapy as post mogamulizumab monotherapy, the efficacy rate and median duration of response tended to be better than in a previous report. 12 Not only efficacy, but also safety profiles are important to evaluate the clinical use of mogamulizumab monotherapy.…”
Section: Discussioncontrasting
confidence: 71%
“…12 Interestingly, in the present case series of MF treated with etoposide-based therapy as post mogamulizumab monotherapy, the efficacy rate and median duration of response tended to be better than in a previous report. 12 Not only efficacy, but also safety profiles are important to evaluate the clinical use of mogamulizumab monotherapy. 5 As the previous phase III, randomized trial suggested, various SAEs occur, but at a lower rate in patients treated with mogamulizumab monotherapy.…”
Section: Discussioncontrasting
confidence: 71%
“…In Japan, oral etoposide (25–50 mg daily for 3 weeks followed by an interval of 1 week) alone or in combination with oral prednisolone (10–20 mg daily) has been used for advanced stage MF/SS refractory to previous therapy 75 . In a recent retrospective study including 13 patients, low‐dose oral etoposide (50 mg every other day ~100 mg daily) showed an ORR of 67% 76 …”
Section: Current Understanding Of Cutaneous Lymphomasmentioning
confidence: 99%
“…75 In a recent retrospective study including 13 patients, low-dose oral etoposide (50 mg every other day ~100 mg daily) showed an ORR of 67%. 76 Gemcitabine has been used for the treatment of a variety of malignant tumors including CTCL. In a phase II trial targeting stage IIB/III MF that had been refractory to previous treatments, gemcitabine showed an ORR of 70% with a CR rate of 10%.…”
Section: E52mentioning
confidence: 99%
“…In a retrospective study of 13 patients with MF conducted in the USA, nine patients (69%) responded to low‐dose etoposide (50 mg every other day to 100 mg daily p.o., or 150 mg once a week i.v. ); median duration of response was 43 weeks 60 …”
Section: Current and Emerging Therapies For Cutaneous Lymphomamentioning
confidence: 99%